2021
DOI: 10.1051/bsgf/2021015
|View full text |Cite
|
Sign up to set email alerts
|

The Beni Bousera marbles, record of a Triassic-Early Jurassic hyperextended margin in the Alpujarrides-Sebtides units (Rif belt, Morocco)

Abstract: The timing and process of exhumation of the subcontinental peridotites of the Gibraltar Arc (Ronda, Beni Bousera) have been repeatedly discussed in the last decades. Here we report on high-grade marbles that crop out around the central and southeastern parts of the Beni Bousera antiform of northern Rif. Instead of being mere intercalations in the granulitic envelope (kinzigites) of the peridotites, as currently admitted, they are localized between the kinzigites and the gneisses of the overlying Filali Unit. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 165 publications
(223 reference statements)
1
1
0
Order By: Relevance
“…Conversely, and in line with Chalouan et al (2008), we adopt here the "Swiss hypothesis" (Trümpy, 1973;Wildi et al, 1977;Nold et al, 1981) that considers the Dorsale as detached from the Alpujarrides-Sebtides on the Middle Triassic pelitic beds. This is consistent with the thinning of the Alpujarride-Sebtide crust and early exhumation of the Ronda-Beni Bousera peridotites underneath (Farah et al, 2021). The pre-orogenic structure of the Alboran Domain passive margin is discussed in Michard et al (2023) and shown consistently hereafter.…”
Section: Generalsupporting
confidence: 78%
“…Conversely, and in line with Chalouan et al (2008), we adopt here the "Swiss hypothesis" (Trümpy, 1973;Wildi et al, 1977;Nold et al, 1981) that considers the Dorsale as detached from the Alpujarrides-Sebtides on the Middle Triassic pelitic beds. This is consistent with the thinning of the Alpujarride-Sebtide crust and early exhumation of the Ronda-Beni Bousera peridotites underneath (Farah et al, 2021). The pre-orogenic structure of the Alboran Domain passive margin is discussed in Michard et al (2023) and shown consistently hereafter.…”
Section: Generalsupporting
confidence: 78%
“…Subsequently, the Sebtides units consist of metamorphic rocks of kinzigites and gneisses surrounded by peridotite materials. Consequently, these deposits are overlain by the Quaternary materials deposits, affected by metamorphism tectonic (Farah et al 2021 andMarrone et al 2021). Therefore, several major contacts, characteristic of the stacking nappes in the internal zones, which crosse-section the Ghomarides and Sebtides units.…”
Section: Geological Tectonics and Geomorphological Analysismentioning
confidence: 99%